THE INTERRELATIONSHIP BETWEEN ANATOMY AND PHYSIOLOGY: FOUNDATIONS FOR UNDERSTANDING THE HUMAN BODY (Modern education and development, 2025)
Anatomy and physiology are two closely related fields that provide a comprehensive understanding of the human body. Anatomy focuses on the structures of body parts, while physiology examines their functions. Understanding their interconnection is crucial for medical education, clinical practice, and research.